TRI-GUNAS (SATTVA, RAJAS AND TAMAS) AND RISK-TAKING BEHAVIOR AMONG UNDERGRADUATE STUDENTS - Kumar Yadav, Santosh; Prakash, Shiv; Kumar Jain, Rajat (International Journal of Research -GRANTHAALAYAH, 2016)
Tri-Gunas is considered an important personality factors in the eastern philosophy. Objective of the present study is to find out co-relation between Tri-Gunas factors of personality and risk- taking behavior among undergraduate students. Sample consists of 192 under graduate students (94 male & 98 female) selected by adopting random sampling method. The tools used for the study are Personality Assessment Profile by Dr. UpendraDhar, Dr. SapanaParashar and Dr. Santosh Dhar and Risk taking Questionnaire constructed by Verendra Sinha and P.N. Arora. Statistical analysis was done by computing person’s product moment co-relation. Findings of the study are - 1) Sattvic personality and risk-taking behavior are not correlated to each other significantly. 2) Rajsic personality and risk-taking behavior are not correlated to each other significantly. 3) Tamsic personality and risk-taking behavior are not correlated to each other significantly in male students but in case of female students there exists a positive and significant co-relation.